Biosafety in hospitals and health areas - Arriciaga, ohana (Revista Universidad de Guayaquil, 2010)
Current information about rules, proceedings, biosecurity standards, legal criteria, hospitalary risk and alert signs currently applied in Ecuador are described. Authors suggest these regulations and reference material are useful to health agency managers to achieve knowledge on biosecurity standards to improve health organization performance required by labor community
Keywords: biosecurity standards; biological hazards; exposure